2017
DOI: 10.5194/bg-2017-91
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of geophysical tools for tree root studies in forest ecosystems in complex soils

Abstract: <p><strong>Abstract.</strong> While semiarid forests frequently colonize rocky substrates, knowledge is scarce on how roots garner resources in these extreme habitats. The Sierra San Miguelito Volcanic Complex in Central Mexico exhibits shallow soils and impermeable rhyolitic-rock outcrops, which impede water movement and root placement beyond the soil matrix. However, rock fractures, exfoliations, and soil pockets potentially permit downward percolation and root growt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Electrical resistivity tomography has also been used in orchards to study soil moisture dynamics and irrigation patterns near cash crops such as fruit trees (Lazzari et al., 2008; Loperte et al., 2006). These studies found an increasing resistivity in the root zone due to drying through root water uptake processes, but some root zones show lower resistivity than the background as shown in Figure 5 (Lazzari et al., 2008; Petersen & Al Hagrey, 2009; Rodríguez‐Robles, Arredondo, Huber‐Sannwald, Ramos‐Leal, & Yépez, 2017; Werban, Attia al Hagrey, & Rabbel, 2008). The low resistivity of fine roots and high resistivity of tree roots reported in the studies discussed above is an indication that roots are a contributing factor, although masked by other factors, as discussed above.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 98%
“…Electrical resistivity tomography has also been used in orchards to study soil moisture dynamics and irrigation patterns near cash crops such as fruit trees (Lazzari et al., 2008; Loperte et al., 2006). These studies found an increasing resistivity in the root zone due to drying through root water uptake processes, but some root zones show lower resistivity than the background as shown in Figure 5 (Lazzari et al., 2008; Petersen & Al Hagrey, 2009; Rodríguez‐Robles, Arredondo, Huber‐Sannwald, Ramos‐Leal, & Yépez, 2017; Werban, Attia al Hagrey, & Rabbel, 2008). The low resistivity of fine roots and high resistivity of tree roots reported in the studies discussed above is an indication that roots are a contributing factor, although masked by other factors, as discussed above.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 98%